Assessing nature exposure: a study on the reliability and validity of a Portuguese version of the nature exposure scale - Picanço, Ana; Arroz, Ana Moura; Tsafack, Noelline; Sánchez, Ana Fuentes; Pereira, Enésima; De Benedictis, Marta; Amorim, Isabel R.; da Luz Melo, Maria; Gabriel, Rosalina (Frontiers in Psychology, 2024)
Engaging with nature has known well-being benefits, but assessing it typically involves estimating green space exposure and outdoor time. The Nature Exposure Scale (NES) uniquely gauges the quality of nature experiences, both deliberate and spontaneous.This study evaluated the NES in Portugal using exploratory and confirmatory factor analyses (PCA and CFA), reliability assessments, and tests of convergent/divergent validity. Data from 558 adults and 241 adolescents (2016-2018) showed strong internal consistency, acceptable correlation values, and robust factor loadings in a unidimensional model. The NES effectively predicted variations in nature exposure across different professional activities.In summary, the 4-item NES is a reliable tool for assessing nature exposure across diverse settings, bridging the gap in the Portuguese context and facilitating cross-cultural research. Its potential in Portuguese-speaking regions warrants further exploration, enhancing our understanding of nature's impact on well-being in varied cultural contexts.